2020
DOI: 10.1098/rspb.2019.2143
|View full text |Cite
|
Sign up to set email alerts
|

Species interactions and environmental context affect intraspecific behavioural trait variation and ecosystem function

Abstract: Functional trait-based approaches are increasingly adopted to understand and project ecological responses to environmental change; however, most assume trait expression is constant between conspecifics irrespective of context. Using two species of benthic invertebrate (brittlestars Amphiura filiformis and Amphiura chiajei ), we demonstrate that trait expression at individual and community levels differs with biotic and abiotic context. We use PERMANOVA to test th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 69 publications
2
11
0
Order By: Relevance
“…Here, we find strong evidence that changes in environmental setting related to inter-annual variations in sea ice alter the benthic community response from seasonal or latitudinal expectation; that is, the expression of climate forcing at the benthos (here, approx. 300 m water depth) is not temporally or spatially homogeneous [97,98] and leads to context-specific changes in species behaviour and related levels of ecosystem functioning [40,99]. At the same time, our analysis confirms the presence of distinct basal infaunal communities and a faunal separation between northern (Arctic) and southern (Atlantic) assemblages at a latitude that corresponds with the operational oceanographic [66] and benthic [56] polar front.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Here, we find strong evidence that changes in environmental setting related to inter-annual variations in sea ice alter the benthic community response from seasonal or latitudinal expectation; that is, the expression of climate forcing at the benthos (here, approx. 300 m water depth) is not temporally or spatially homogeneous [97,98] and leads to context-specific changes in species behaviour and related levels of ecosystem functioning [40,99]. At the same time, our analysis confirms the presence of distinct basal infaunal communities and a faunal separation between northern (Arctic) and southern (Atlantic) assemblages at a latitude that corresponds with the operational oceanographic [66] and benthic [56] polar front.…”
Section: Discussionsupporting
confidence: 57%
“…Changes in species and functional groups between seasons, attributed to the presence of more labile organic matter reaching the seafloor in summer, provide anecdotal support for this assertion [64]. Indeed, recent work has shown that such spatial-temporal changes are linked to the functional traits of organisms because environmental context—in particular sea ice and bottom water temperature [35]—influences the trait expression of individuals which, in turn, dictates net community-level behaviour and ecosystem functioning [99,108]. Comparison of our northern and southern faunal clusters provide some insight as to what may lie in store (elevated bioturbation and nutrients) as organisms adapted to seasonally ice-covered Arctic shelf habitats are replaced (local extinction) by southern Atlantic species, but it would be naïve to assume that this transition in faunal composition will define ecosystem functioning.…”
Section: Discussionmentioning
confidence: 99%
“…Also, recent studies relate the intensity of bioturbation to the species metabolism, which is temperature-sensitive 39 , 43 , 44 , reinforcing our initial hypothesis to expect differences due to the warming. However, the community response would be influenced by density-dependent factors and potential species interactions 45 , 46 , which may hinder the detection of a clear pattern.…”
Section: Discussionmentioning
confidence: 99%
“…Still, to gain important insights into the ecosystem functions and resilience of Indian vents, the functional trait repertoire needs to be substantially expanded to represent a comprehensive collection of Indian vent animals and include better estimates of the variability associated with each of their trait. Functional traits related to species morphologic or behavioral phenotypes are context dependent and their variation can affect our predictions of ecosystem function (Cassidy et al, 2020). Hence, more research needs to be conducted to gather baseline information on the biology of Indian vent macrofauna, and communities need to be surveyed further to provide reliable estimates for the spatial and temporal variance of their traits.…”
Section: How Diverse and Variable Are Community Functional Traits?mentioning
confidence: 99%